Organic-inorganic nanostructured multilayers for calcium phosphate biomineralization - Leite, Álvaro J. (2013)
The weak fixation of biomaterials within the bone structure is one of the major reasons of implants failures. Calcium phosphate (CaP) coatings are used in bone tissue engineering to improve implant osseointegration by enhancing cellular adhesion, proliferation and differentiation, leading to a tight and stable junction between implant and host bone. It has also been observed that materials compatible with bone tissue either have a CaP coating or develop such a calcified surface upon implantation. Thus, the development of bioactive coatings becomes essential for further improvement of integration with the surrounding tissue. However, most of current applied CaP coatings methods (e.g. physical vapor deposition), cannot be applied to complex shapes and porous implants, provide poor structural control over the coating and prevent incorporation of bioactive organic compounds (e.g. antibiotics, growth factors) because of the used harsh processing conditions. Layer-by-layer (LbL) is a versatile technology that permits the building-up of multilayered polyelectrolyte films in mild conditions based on the alternate adsorption of cationic and anionic elements that can integrate bioactive compounds. As it is recognized in natureâ s biomineralization process the presence of an organic template to induce mineral deposition, this work investigate a ion based biomimetic method where all the process is based on LbL methodology made of weak natural-origin polyelectrolytes. A nanostructured multilayer component, with 5 or 10 bilayers, was produced initially using chitosan and chondroitin sulphate polyelectrolyte biopolymers, which possess similarities with the extracellular matrix and good biocompatibility. The multilayers are then rinsed with a sequential passing of solutions containing Ca2+ and PO43- ions. The formation of CaP over the polyelectrolyte multilayers was confirmed by QCM-D, SEM and EDX. The outcomes show that 10 polyelectrolyte bilayer condition behaved as a  better site for initiating the formation of CaP as the precipitation occur at earlier stages than in 5 polyelectrolyte bilayers one. This denotes that higher number of bilayers could hold the CaP crystals more efficiently. This work achieved uniform coatings that can be applied to any surface with access to the liquid media in a low-temperature method, which potentiates the manufacture of effective bioactive biomaterials with great potential in orthopedic applications.